Effect of Acetic Acid Administration in Drinking Water on Performance and Growth Characteristics and Ileal Microflora of Broiler Chickens - M. R. Akbari (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2004)
This experiment was conducted to evaluate the effects of adding acetic acid to drinking water on the performance and ileal microorganisms of broiler chickens. In a completely randomized design with 5 treatments and 5 replicates, 300 day-old commercial mail broiler chicks (ROSS) were divided into 25 groups, 12 chicks per group. Each of the five levels of acetic acid added to drinking water (0.0, 0.1, 0.2, 0.3, and 0.4%) were given to five replicates for a period of 21 days. All groups were fed a practical corn-soybean based diet. During the experiment, chickens were not fed any antibiotics or coccidiostats. The diet formulation for all groups was the same. At 14 and 28 days of age, one chicken of each replicate was weighed and killed by cervical dislocation. Ileal contents were collected and used for microbial evaluation. At 49 days of age, one bird from each pen was killed to weigh gastrointestinal tract, liver, pancreas and abdominal fat. The number of total aerobes and colliforms per gram of ileal contents were enumerated on the appropriate bacteriological media. There was no significant difference in feed intake, weight gain, feed to gain ratio, live body weight, gastrointestinal tract, abdominal fat, liver and pancreas weights (p>0.05). Also, the differences among treatments for total aerobe and coliform counts were not significant (p>0.05). Under the conditions of this study, addition of acetic acid as an organic acid into drinking water at the levels used could not affect the performance and ileal microbial counts of chickens.